Deconstruction of plant biomass by autohydrolysis - Carlos, Rute das Neves Sarabando (2018)
The search for better technologies for upgrading biomass wastes has received increasing attention in the recent years. Special consideration has to be given to the hemicellulosic fraction, one of the more challenging fractions. In this work, two biologically different waste materials were iorefinery concept: the materials derived from the forestry processing of the cypress cedar of Goa (Cupressus lusitanica Mill.), namely chips, bark, leaves and cones, and the wastes of the watermelon (Citrullus lanatus) industrial processing (rinds). The chemical composition of all materials was characterized taking special attention to the extractives content and to the structural polysaccharides and lignin and the autohydrolysis process was optimized aiming for the production of novel oligosaccharides. The autohydrolysis process presented a high selectivity towards hemicelluloses, yielding oligosaccharides in high concentrations, especially for the chips of cypress cedar of Goa. The oligosaccharides were characterized regarding their chemical composition and their stability under different temperature and pH values. Their potential industrial applications, namely for the food industry, are also presented and discussed. As a preliminary evaluation of the integrated upgrade of these materials, the use of biomass from cypress cedar of Goa as a source of essential oils and the digestibility of the cellulose present in the residual biomass derived from the autohydrolysis treatments as a source of glucose for fermentation were also tested and are discussed.